Consumption and identity representations in Brazil's most famous fashion blogs - Schneider, Thaissa (2015)
Given the current growth of fashion blogs in Brazil, this research aims to describe how heir authors have become opinion leaders, influencing readers and dictating trends. The blogosphere -the universe and culture of blogs –is a complex and extraordinarily dynamic system, as well as fashion and the polarization of trends and behavior. In this sense, it is proposed as an object of study this new communication tool and its potential impact on various spheres of human life. We opted to use the literature that provided theoretical basis, and field research, using the technique of case study. The case study was executed considering Brazil’s most relevant fashion blogs, in order to understand its structure, functional organization and interaction with users. Based on that, we observed the role of so-called bloggers as reference groups, analyzing the process of adoption and diffusion of fashion through the interactivity that suggests unique ways of hypermedia. The study contributed to the analyzes of this communication instrument, as it included theoretical research on digital interactions and foundation on blogs, its history, structure, functions and multiplicity of uses.